Helping with the kids? How family-friendly workplaces affect parental well-being and behavior - Verena Lauber; Johanna Storck (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Despite political efforts, balancing work and family life is still challenging. This paper provides novel evidence on the effect of firm level interventions that seek to reduce the work-life conflict. The focus is on how a specific workplace policy, namely childcare support, affects the well-being, working time, and caring behavior of mothers with young children. We exploit the fact that since the mid 2000s an increasing number of employers have become proactive and implemented more family-friendly workplaces. These changes over time allow us to identify causal effects of childcare support using a difference-in-differences approach combined with matching. Based on a large panel dataset on families with children in Germany (FiD), we find evidence pointing to welfare enhancing effects of childcare support, as it strongly increases both childcare satisfaction and job satisfaction. In particular mothers who worked limited hours before the introduction, possibly due to constraints, increase their working time and use formal care more intensively. Satisfaction levels are also more strongly affected if mothers are career-orientated. In comparison, flexible work schedules, another family-friendly policy, only affect job satisfaction. Paternal well-being and behavior is not affected by the workplace policy.
Keywords: I31; J13; J22; J28; 330; family-friendly workplace policies; well-being; work-life balance; difference-in-differences; matching